Desafios e oportunidades para o acesso universal à energia elétrica na Amazônia - MUNIZ, Rafael Ninno (Universidade Federal do Pará, 2017)
The Brazilian energy planning has been progressively emphasizing the use of renewable energy sources, however for some initiatives such as the Light for All Program, these energy alternatives are being treated as a secondary activity and difficult to implement. This work aims to analyze how the Brazilian government has been adapting its institutional structure, technology and funding to provide universal access to electricity in remote areas. According to official information, this initiative has proven effective in its first phase, which was developed by the extension of conventional network. However, the study concludes that the program is currently not converges to full compliance with the access to electricity in remote areas in the Amazon and three main challenges were identified. There is a need for adjustment of current institutional structures, harmonize technologies to the regional context and use government funds more effectively. The research points out ways and alternatives to what is being done in isolated systems, and presents two case studies which have been applied to decentralized power generation with renewable sources of biomass in isolated community, and the energy utilization of municipal solid waste in the municipality belonging to the isolated system. These practical examples are proposed to contribute to the results of the study for the development of public policies, research projects, meet technology providers and promote energy and residuary solutions for municipalities and communities belonging to national isolated system, aiming to achieve universal access to energy electricity in remote areas in the Amazon.